A new theropod dinosaur from the early cretaceous (Barremian) of Cabo Espichel, Portugal: Implications for spinosaurid evolution - Mateus, Octávio; Estraviz-López, Darío (PLOS ONE, 2022)
Spinosaurids are some of the most enigmatic Mesozoic theropod dinosaurs due to their unique adaptations to aquatic environments and their relative scarcity. Their taxonomy has proven to be especially problematic. Recent discoveries from Western Europe in general, specifically Iberia, provide some of the best specimens for the understanding of their phylogeny, leading to the description of the spinosaurid Vallibonavenatrix cani and the recognition of the Iberian dinosaur Camarillasaurus cirugedae as one of them. Portuguese associated spinosaurid remains (ML1190) from the Papo Seco Formation (early Barremian) were previously assigned to Baryonyx walkeri but new material recovered in 2020 along with new phylogenetic analyses suggests a different phylogenetic placement, making their revision necessary. Here we show that these remains are not attributable to Baryonyx walkeri, but to a new genus and species, Iberospinus natarioi, gen. et sp. nov. The new taxon is characterized by the presence of a single Meckelian foramen in the Meckelian sulcus, a straight profile of the ventral surface of the dentary and a distal thickening of the acromion process of the pubis between other characters. Iberospinus natarioi is recovered as a sister taxon of the clade formed by Baryonyx and Suchomimus, and outside Spinosaurinae when Vallibonaventrix cani is excluded from the analysis. The description of this taxon reinforces Iberia as a hotspot for spinosaur biodiversity, with several endemic taxa for the region. As expected for the clade, the dentary displays a highly vascularized neurovascular network. The morphometric analysis of parts of the skeleton (pedal phalanx and caudal vertebrae, among others) shows an intermediate condition between basal tetanurans and spinosaurines.